Creating new 3D forms in collaborative product design - Yang, Weishu; Lahti, Henna; Seitamaa-Hakkarainen, Pirita (Design and Technology Education: An International Journal, 2022)
In collaborative design settings, designers communicate and explicate their ideas visually and verbally in order to reach a shared understanding. The verbal exchanges of group members engaged in a joint design task provide rich data regarding the design activities being undertaken by the group members. In addition, sketching and modelling are recognized as essential for designers to examine and produce design ideas at the very beginning of the design process. This exploratory case study focuses on collaborative design activities and problem–solution co-evolution among the various design disciplines that students engage in during their product design processes. Nine students from three design disciplines (interior design, product design, and graphic design) participated in a workshop providing knowledge about 3D modelling, following which they undertook a re-design task to develop a new 3D form of a detergent bottle. The research data consisted of video recordings and sketches, and the analysis focused on the progress of the design processes and the differences between the groups. The results highlight that the creation of new 3D forms was based on intensive reformulation activities such as setting new problem expressions or modifying existing ones. This kind of re-design task, which presented constraints in terms of developing a new 3D form within the prescribed requirements, served as a good exercise through which to practice co-evolution because it drove the design activities towards a balance of transitions in the problem and solution spaces.